Parents' experiences of complementary feeding among a United Kingdom culturally diverse and deprived community - Erica Jane Cook; Faye Caroline Powell; Nasreen Ali; Catrin Penn‐Jones; Bertha Ochieng; Gurch Randhawa (Wiley, 2021)
Abstract Complementary feeding practices and adherence to health recommendations are influenced by a range of different and often interrelating factors such as socio‐economic and cultural factors. However, the factors underlying these associations are often complex with less awareness of how complementary feeding approaches vary across the UK's diverse population. This paper describes a qualitative investigation undertaken in a deprived and culturally diverse community in the UK which aimed to explore parents' knowledge, beliefs and practices of complementary feeding. One hundred and ten mothers and fathers, self‐identified as being White British, Pakistani, Bangladeshi, Black African/Caribbean or Polish took part in twenty‐four focus group discussions, organised by age group, sex and ethnicity. The findings revealed that most parents initiated complementary feeding before the World Health Organisation (WHO) recommendation of 6 months. Early initiation was strongly influenced by breast feeding practices alongside the extent to which parents believed that their usual milk; that is, breastmilk or formula was fulfilling their infants' nutritional needs. The composition of diet and parents' approach to complementary feeding was closely aligned to traditional cultural practices; however, some contradictions were noted. The findings also acknowledge the pertinent role of the father in influencing the dietary practices of the wider household. Learning about both the common and unique cultural feeding attitudes and practices held by parents may help us to tailor healthy complementary feeding advice in the context of increasing diversity in the United Kingdom.